2014
DOI: 10.1089/ars.2013.5334
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Response of Mitochondrial Biogenesis to Oxidative Stress in Visceral Fat of Diet-Induced Obesity Mice

Abstract: Aims: Studies in skeletal muscle demonstrate a strong association of mitochondrial dysfunction with insulin resistance (IR). However, there is still a paucity of knowledge regarding the alteration of mitochondria in adipose tissue (AT) in the pathogenesis of IR in obesity. We investigated the mitochondrial biogenesis in visceral fat (VF) and subcutaneous fat (SF) in C57BL/6J mice fed a high-fat high-sucrose diet for 12 months. Results: Impairment of glucose tolerance and insulin sensitivity developed after 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…21 Mitochondrial biogenesis is orchestrated by a transcriptional cascade involving peroxisome proliferatoractivated receptor g coactivators 1a (PGC-1a), PGC-1b, PGC-1-related coactivator (PRC), estrogen-related receptor a (ERRa), nuclear respiratory factors 1 (NRF1) and 2 (NRF2) and mitochondrial transcription factor A (Tfam). 22 Mitochondrial biogenesis was enhanced in WAT of the AdSod2 KO mice and was associated with increased transcription of PGC-1a, PGC-1b and nuclear and mitochondrial-encoded genes, implying a causal role for ROS in the induction of mitochondrial biogenesis.…”
Section: Adsod2 Ko Increases Energy Expenditure and Protects Against Diomentioning
confidence: 99%
“…21 Mitochondrial biogenesis is orchestrated by a transcriptional cascade involving peroxisome proliferatoractivated receptor g coactivators 1a (PGC-1a), PGC-1b, PGC-1-related coactivator (PRC), estrogen-related receptor a (ERRa), nuclear respiratory factors 1 (NRF1) and 2 (NRF2) and mitochondrial transcription factor A (Tfam). 22 Mitochondrial biogenesis was enhanced in WAT of the AdSod2 KO mice and was associated with increased transcription of PGC-1a, PGC-1b and nuclear and mitochondrial-encoded genes, implying a causal role for ROS in the induction of mitochondrial biogenesis.…”
Section: Adsod2 Ko Increases Energy Expenditure and Protects Against Diomentioning
confidence: 99%
“…Contrary to the limited data on humans, several animal studies using either genetic or dietary models of obesity have clearly showed a reduction in mitochondrial oxidative capacity in WAT (Wilson-Fritch et al 2003;Choo et al 2006); however, it remains unclear whether these changes are causal or secondary to the metabolic alterations associated with obesity, such as insulin resistance and diabetes. Indeed, studies performed on high-fat-fed animals revealed that mitochondrial dysfunction might result from altered systemic insulin sensitivity and glucose tolerance in mice (Sutherland et al 2008;Wang et al 2014). The mechanisms responsible for diminished mitochondrial oxidative capacity in WAT with obesity are not well characterized but may involve enhanced inflammation, higher oxidative damage, ER stress, reduced biogenesis and impaired mitochondrial dynamics (Valerio et al 2006).…”
Section: Mitochondrial Dysfunction In White Adipose Tissuementioning
confidence: 99%
“…The mechanisms responsible for diminished mitochondrial oxidative capacity in WAT with obesity are not well characterized but may involve enhanced inflammation, higher oxidative damage, ER stress, reduced biogenesis and impaired mitochondrial dynamics (Valerio et al 2006). Indeed, increased ROS generation in epididymal fat preceded mitochondrial impairments in high-fat-fed mice (Wang et al 2014).…”
Section: Mitochondrial Dysfunction In White Adipose Tissuementioning
confidence: 99%
See 2 more Smart Citations